Treg engage lymphotoxin beta receptor for afferent lymphatic transendothelial migration - C. Colin Brinkman (Nature Portfolio, 2016)
Lymphotoxin regulates lymphoid organ architecture and adhesion molecules involved in lymphocyte trafficking. Here the authors show that lymphotoxin produced by regulatory T cells promotes their migration to the draining lymph nodes by engaging its cognate receptor on lymphatic endothelial cells.